Surgical Treatment of Supracondylar Humeral Fractures in a Freestanding Ambulatory Surgery Center is as Safe as and Faster and More Cost-Effective Than in a Children's Hospital. Issue 6 (July 2018) - Rider, Carson M.; Hong, Victor Y.; Westbrooks, Timothy J.; Wang, Jiajing; Sheffer, Benjamin W.; Kelly, Derek M.; Spence, David D.; Flynn, John M.; Sawyer, Jeffrey R.
Abstract : Background: Despite an 88% increase in the number of pediatric fractures treated in ambulatory surgery centers (ASCs) over a 10-year period, few studies have compared outcomes of fracture treatment performed in a freestanding ASC compared with those performed in the hospital (HOSP) or hospital outpatient department (HOPD). The purpose of this study was to compare clinical and radiographic outcomes, treatment times, and costs for treatment of Gartland type II supracondylar humeral (SCH) fracture in the ASC, HOSP, and HOPD. Methods: Retrospective review identified pediatric patients with isolated Gartland type II SCH fractures who had closed reduction and percutaneous pinning (CRPP) by board-certified orthopaedic surgeons from January 2012 to September 2016. On the basis of the location of their treatment, patients were divided into 3 groups: HOSP, HOPD, and ASC. All fractures were treated with CRPP under fluoroscopic guidance using 2 parallel or divergent smooth Kirschner wires. Radiographs obtained before and after CRPP and at final follow-up noted the anterior humeral line index (HLI) and Baumann angle. Statistical analysis compared all 3 groups for outcomes, complications, treatment time/efficiency, and charges. Results: Record review identified 231 treated in HOSP, 35 in HOPD, and 50 in ASC. Radiographic outcomes in terms of Baumann angle and HLI did not differ significantly between the groups at any time point except preoperatively when the HLI for the HOSP patients was lower ( P =0.02), indicating slightly greater displacement than the other groups. Overall complication rates were not significantly different among the groups, nor were occurrences of individual complications. The mean surgical time was significantly shorter ( P <0.0001) in ASC patients than in HOPD and HOSP patients, and total charges were significantly lower ( P <0.001). Conclusions: Gartland type II SCH fractures can be safely treated in a freestanding ASC with excellent clinical and radiographic outcomes equal to those obtained in the HOSP and HOPD; treatment in the ASC also is more efficient and cost-effective. Level of Evidence: Level III—retrospective comparative study.